PEMBUATAN GENERATOR OZON SEBAGAI AGEN OKSIDATOR TEMBAGA PADA PRODUKSI TEMBAGA SULFAT - Yunus, Yadi (ReTII, 2022)
Ozone with high concentration as an oxidizing copper metal, can be produced in situ and sustainably using an ozone generator. In this research, an integrated ozone generator with oxygen concentrator has been made in order to supply high concentrations of oxygen to the ozone generator tube. The method for producing ozone is by passing O2 (oxygen) gas on the corona discharge, which is generated using a high voltage which is made by oscillating DC electric voltage into a signaled voltage (AC) which is then multiplied by the voltage into a high voltage using a car ignition coil. To oscillate the DC voltage, an oscillator based on IC555 is equipped with a 100k potentiometer as a frequency regulator and the output signal voltage, which is then amplified with a DA1047 transistor, and this amplified signal is input to the primary side of the car coil. In addition, with the aim of increasing ozone products, this ozone generator is equipped with an oxygen concentrator along with a valve for regulating the flow rate of the input air as its raw material. From the test experiment when the primary coil input voltage variation is 8, 10, 12, 14 and 16 volts, and with the input air flow rate (2.5 ; 5; 7.5 ; 10; 20 and 30 liters/minute), and each time The experiment used 5 minutes, the result was that the highest Ozone production was 0.038 ppm/minute achieved at a coil input voltage of 16 volts and an air flow rate of 7.5 L/minute.